The investigation of giant magnetic moment in ultrathin Fe3O4 films - Guan, Xiaofen; Zhou, Guowei; Xue, Wuhong; Quan, Zhiyong; Xu, Xiaohong (APL materials, 2016)
The magnetic and transport properties of Fe3O4 films with a series of thicknesses are investigated. For the films with thickness below 15 nm, the saturation magnetization (Ms) increases and the coercivity decreases with the decrease in films’ thickness. The Ms of 3 nm Fe3O4 film is dramatically increased to 1017 emu/cm3. As for films’ thickness more than 15 nm, Ms is tending to be close to the Fe3O4 bulk value. Furthermore, the Verwey transition temperature (Tv) is visible for all the films, but suppressed for 3 nm film. We also find that the ρ of 3 nm film is the highest of all the films. The suppressed Tv and high ρ may be related to the islands morphology in 3 nm film. To study the structure, magnetic, and transport properties of the Fe3O4 films, we propose that the giant magnetic moment most likely comes from the spin of Fe ions in the tetrahedron site switching parallel to the Fe ions in the octahedron site at the surface, interface, and grain boundaries. The above results are of great significance and also provide a promising future for either device applications or fundamental research.